Pome and Stone Fruits: Safe Handling Practices for Consumers - Amy Simonne (EDIS, 2007)
Revised! FCS8742, a 2-page fact sheet by Amy Simonne, lists steps that consumers can take to reduce their risk of foodborne illness from fresh produce. Published by the UF Department of Family, Youth and Community Sciences, March 2006.